Passive Heat Exposure Alters Perception and Executive Function - Malcolm, Rachel A.; Cooper, Simon; Folland, Jonathan P.; Tyler, Christopher J.; Sunderland, Caroline (Frontiers in Physiology, 2018)
Findings regarding the influence of passive heat exposure on cognitive function remain equivocal due to a number of methodological issues including variation in the domains of cognition examined. In a randomised crossover design, forty-one male participants completed a battery of cognitive function tests (Visual Search, Stroop, Corsi Blocks and Rapid Visual Information Processing (RVIP) tests) prior to and following 1 h of passive rest in either hot (39.6±0.4 °C, 50.8±2.3 % Rh) or moderate (21.2±1.8 °C, 41.9±11.4 % Rh) conditions. Subjective feelings of heat exposure, arousal and feeling were assessed alongside physiological measures including core temperature, skin temperature and heart rate, at baseline and throughout the protocol. Response times were slower in the hot trial on the simple (main effect of trial, P<0.001) and complex (main effect of trial, P<0.001) levels of the Stroop test (Hot: 872±198 ms; Moderate: 834±177 ms) and the simple level of the visual search test (Hot: 354 ±54 ms; Moderate: 331±47 ms) (main effect of trial, P<0.001). Participants demonstrated superior accuracy on the simple level of the Visual Search test in the hot trial (Hot: 98.5 ± 3.1%; Moderate: 97.4 ± 3.6%) (main effect of trial, P=0.035). Participants also demonstrated an improvement in accuracy on the complex level of the visual search test following 1 h passive heat exposure (Pre: 96.8 ± 5.9 %; Post: 98.1 ± 3.1 %), whilst a decrement was seen across the trial in the moderate condition (Pre: 97.7 ± 3.5; Post: 97.0 ± 5.1 %) (time*trial interaction, P=0.029). No differences in performance were observed on the RVIP or Corsi Blocks tests (all P>0.05). Subjective feelings of thermal sensation and felt arousal were higher, feeling were lower in the hot trial, whilst skin temperature, core temperature and heart rate were higher (main effects of trial, all P<0.001). The findings of the present study suggest that response times for perception and executive function tasks are worse in the heat. An improvement in accuracy on perceptual tasks may suggest a compensatory speed-accuracy trade-off effect occurring within this domain, further highlighting the task dependant nature of heat exposure on cognition.